การพัฒนารูปแบบการเรียนรู้โมเดลธุรกิจด้วยเทคนิคการตั้งคำถาม 5W1H ร่วมกันบนเว็บ เพื่อส่งเสริมความสามารถในการคิดวิเคราะห์สำหรับนิสิตนักศึกษาระดับปริญญาบัณฑิต - เสรีเสถียรทรัพย์ โสภณ; สงคราม เนาวนิตย์ (An Online Journal of Education, 2018)
The purpose of this research study was to development of learning business model using 5W1H questions with collaborative web to enhance analytical thinking ability of undergraduate students. The sample for the survey consisted of nine experts in the field of educational technology and web-based Instruction, business model, analytical thinking ability, collaborative learning, and 5W1H questions. The research instruments consisted of the expert interview form and the model evaluation form. The result of this study was the model comprised of nine elements and three steps. The nine elements were: (1) Customer Segments; (2) Value Propositions; (3) Channels; (4) Customer Relationships; (5) Revenue Streams; (6) Key Resources; (7) Key Activities; (8) Key Partners (9) Cost Structure. The three steps were: (1) The pre-learning phase; (2) The during learning phase; (3) The post-learning phase.